Experimental Study on Stability Analysis of a Structure during Excavation beneath This Structure - Yichen Miao; Baoxian Liu; Changwu Liu; Zhile Shu; Haikuan Wu (Advances in Civil Engineering)
In order to create more underground space, it was important to investigate the impact of excavation on the preexisting building. In this paper, a scale model test was conducted to analyze the stability of the structure during excavation. The model consisted of underpinning piles preinstalled in clay, with a reinforced concrete building placed on underpinning piles. The strain and settlement of the structure were observed to reveal the time settlement of columns and the time strain of beams, columns, and piles during excavation. The results showed that the strain change of beams was small, and strain values of columns were getting higher. And underpinning piles had great strain variations. They were of great significance to underpinning design and engineering practice.